Rozwój szkolnictwa podstawowego w gminie Będzino w latach 1945–1954 - Skonieczny, Tomasz (Biuletyn Historii Wychowania, 2013)
Education on the area of post-war community Będzino (1945–1954) The article is based on the archives portraying the formation process of Polish schools and cultural institutions as a result of the transformations of the educational system. It presents the condition of the teaching staff and the financial base related to the density of population. The author pays attention to such problems as the lack of staff, funds and equipment. He discusses the forms of co-operation with parents and the society, the participation in all-Polish actions organized by state authorities, especially in the action of fighting illiteracy. The supplement includes the schedule and the curriculum from those times. The article is concluded with the description of the end of the existence of the community of Będzino in its primitive, post-war shape.